Governance Implications of the Relationship between Psychological Contract Fulfillment and Job Satisfaction of Competition Volunteers - Shuhua Xia, Mingliang Li (Forest Chemicals Review)
Event volunteers are an important group of event service guarantee. With the help of psychological contract theory, the discussion on the impact of event organizers’ contract performance and event volunteers’ contract performance on the job satisfaction of event volunteers can provide more comprehensive governance suggestions for event organizers. 287 volunteers who participated in the 11th National Traditional Ethnic Minority Sports Games were selected to compile psychological contract performance scale and job satisfaction scale. AMOS26.0 and SPSS 22.0 were used to conduct correlation analysis and hierarchical regression analysis to explore the relationship between variables. The results are as follows :(1) there is a significant positive predictive effect on volunteer job satisfaction; (2) The performance of event organizer’s responsibility has a significant positive predictive effect on volunteer job satisfaction, but lower than the performance of event volunteer’s responsibility; (3) the volunteer duty and the organizers of the event interaction on job satisfaction has to fulfill obligations, namely the contract of volunteers and the organizers of the event contract are high, the volunteer job satisfaction is highest, and when the tournament volunteers contract is high, the event organizer contract low, lowest event volunteer job satisfaction. Therefore, it is necessary to pay attention to the impact of event volunteers’ fulfillment of their responsibilities on job satisfaction. Attach importance to the performance of the event organizers’ responsibilities to the event volunteers; Pay attention to the performance of the responsibilities of the event organizer should match that of the event volunteers.